Quantitative Analysis of Buddhist Sunday School Teacher Performance in terms of Organizational Culture and Work Discipline in Jakarta - Muljadi; P Prita; Y Lawalata; Siska; Hendrian Yonata (Budapest International Research and Critics University, 2022)
Teacher performance is the achievement of a teachers, the result of their work in carrying out all tasks that are charged to them based on their abilities, experience, sincerity and timeliness in accordance with the goals of the organization which are very important to achieve education goals. From the initial survey, it has been found that teacher's performance still didn’t meet expectations. This research aims to find efforts to improve teacher performance, by identification the strengths of relationship between organizational culture, work discipline, and job satisfaction both individually and simultaneously with teacher's performance. The results of this study indicate that: 1) there is a positive relationship between organizational culture and teacher performance with the correlation coefficient ry1 = 0,328 (ρ<0,01), 2) there is a positive relationship between work discipline and teacher performance with correlation coefficient ry2 = 0,796(ρ<0,01), 4) there is positive correlation between organizational culture and work discipline together with teacher performance, with correlation coefficients ρy12=0,436 (ρ<0,01), .This means that teacher performance can be improved through the development of organizational culture, work discipline and job satisfaction both individually and jointly.